The agency cost of investing in ethical funds: A style analysis approach - Hande Ayaydın Hacıömeroğlu; Seza Danışoğlu; Z. Nuray Güner; Baki Cem Şahin (Borsa Istanbul Review, 2022)
This study aims to determine whether ethical funds make portfolio choices in line with their investment mandates. Our results show that during the first half of the sample period, it is much more difficult to distinguish the investment styles of ethical and conventional funds. The potential for ethical fund investors to face agency conflicts from investing in portfolios that are not necessarily in line with their preferences based on environmental, social, and governance (ESG) criteria is higher in the earlier years. In the second half of the sample period, ethical funds appear to invest more in large stocks that have higher ESG ratings than their conventional counterparts. Even though both fund classes have decreased their allocation to ESG-based investment alternatives in recent years, they seem to have slightly more distinct investment styles.